The Effect of The Rebozo (OLeS) Technique on The Low Back Pain of Pregnant Women at Aikmual Public Health Center - Wahyuni, I Gusti Ayu Putu Sri; Saudia , Baiq Eka Putri; Najahah, Imtihanatun (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2024)
Initial survey data at the Aikmual Public Health Center found that 90% of pregnant women in the third trimester experienced low back pain. Almost all pregnant women were given a traditional massage from a shaman which is called Orah Lempot Sasak (OLeS) and a traditional technique called Rebozo. In this study, researchers will provide a combination of the Rebozo Technique with the Orah Lempot Sasak tradition which is usually carried out by belian or birth attendants in the Sasak tribe. This research aims to analyze the effect of the combination of the Ribozo technique and the Orah Lempot Sasak tradition on reducing low back pain in third trimester pregnant women. This study is a pre-experimental study with control group. The respondents were 30 pregnant women who were in 3rd trimester and experience low back pain. The control group was given common pregnancy exercise, while the intervention group was given the Rebozo combined with Orah Lempot Sasak (OLeS). The research results showed a significant effect of using the Rebozo Orah Lempot Sasak combination on reducing low back pain in pregnant women in the third trimester with a P value of 0.001. The traditional based treatment, which is combination of Rebozo and Orah Lempot Sasak effective in reducing low back pain in third trimester pregnant women.